Celestial Lw 1+∞ charges from a twistor action - Kmec, A; Mason, L; Ruzziconi, R; Srikant, AY (Springer, 2024)
The celestial Lw1+∞ symmetries in asymptotically flat spacetimes have a natural geometric interpretation on twistor space in terms of Poisson diffeomorphisms. Using this framework, we provide a first-principle derivation of the canonical generators associated with these symmetries starting from the Poisson BF twistor action for self-dual gravity. We express these charges as surface integrals over the celestial sphere in terms of spacetime data at null infinity. The connection between twistor space and spacetime expressions at I is achieved via an integral formula for the asymptotic Bianchi identities due to Bramson and Tod. Finally, we clarify how Lw1+∞ transformations are symmetries of gravity from a phase space perspective by showing the invariance of the asymptotic Bianchi identities.